PEMBINAAN NARAPIDANA DITINJAU DARI SEGI TUJUAN PEMIDANAAN PADA RUTAN KLAS II B BOYOLALI - THOMAS, M AGUS (Dinamika Hukum, 2019)
The purpose of this study is to describe the legal provisions and the implementation of prisoner guidance in RUTAN KLAS II B BOYOLALI. Besides analyzing the constraints in implementing prisoner guidance, especially in RUTAN KLAS IIB BOYOLALI. Research background that RUTAN is an organizing system for various resources in it (infrastructure, prisoners, etc.). The development of prisoners in the RUTAN aims to make prisoners better after returning to the community. Guidance for prisoners in RUTAN is carried out in accordance with applicable legal provisions. This coaching effort is carried out so that the imprisonment (imprisonment) harmony with the purpose of the imposition of a criminal that is for rehabilitation, reeducation and socialization. The research method consists of the type of research is normative juridical which is equipped with empirical data through observation. The nature of the research is descriptive. More data needed is secondary data. How to collect data with literature studies and observations. The method of data analysis is done by qualitative methods. The results of the study show that the implementation of prisoner coaching is carried out in accordance with applicable regulations in RUTAN. The coaching method is carried out with a model of direct interaction that is familial between the supervisor and prisoner officers. In addition, the coaching method is persuasive to improve behavior patterns through examples and exemplary. The philosophy of coaching is treating prisoners as human beings who have the potential and self-esteem with the same rights and obligations as other human beings. Coaching is carried out a plan, continuously and systematically. The obstacle in conducting coaching is the existence of excessive capacity, this affects the effectiveness of coaching carried out. Key words : Convicting Prisoners, Purpose of Sentencing, RUTAN Klas II B Boyolali.